2007
DOI: 10.1016/j.cropro.2007.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Smallholder vegetable farmers in Northern Tanzania: Pesticides use practices, perceptions, cost and health effects

Abstract: Small-scale farmers in Northern Tanzania grow vegetables that include tomatoes, cabbages and onions and use many types of pesticides to control pests and diseases that attack these crops. Based on the use of questionnaires and interviews that were conducted in Arumeru, Monduli, Karatu, and Moshi rural districts, this study investigates farmers' practices on vegetable pest management using pesticides and related cost and health effects. The types of pesticides used by the farmers in the study areas were insecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
236
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 325 publications
(303 citation statements)
references
References 17 publications
20
236
0
4
Order By: Relevance
“…Empirically, specific studies have shown the high human and environmental risks of unsafe use of pesticides in many African countries such as Ghana (Ntow et al 2006), Tanzania (Ngowi et al 2007), Botswana (Obopile et al 2008), Ethiopia (Jansen and Harmsen 2011), Benin (Ahouangninou et al 2012), Uganda (Kateregga 2012), Kenya (Macharia et al 2013). Other parts of sub-Saharan Africa have similar problems with the widespread use of highly toxic and illegal pesticides (Ecobichon 2001;Williamson et al 2008;Handford et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Empirically, specific studies have shown the high human and environmental risks of unsafe use of pesticides in many African countries such as Ghana (Ntow et al 2006), Tanzania (Ngowi et al 2007), Botswana (Obopile et al 2008), Ethiopia (Jansen and Harmsen 2011), Benin (Ahouangninou et al 2012), Uganda (Kateregga 2012), Kenya (Macharia et al 2013). Other parts of sub-Saharan Africa have similar problems with the widespread use of highly toxic and illegal pesticides (Ecobichon 2001;Williamson et al 2008;Handford et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In African countries, many government extension programs encourage the use of pesticides (Ngowi et al 2007;Kateregga 2012). Also Ethiopian farmers have been stimulated to use pesticides as the only option for crop protection, mainly through advertising pesticide use by retailers and extension officers.…”
Section: Using Practicesmentioning
confidence: 99%
See 2 more Smart Citations
“…Less than one percent of pesticides applied to the agriculture reach their pests, and more than 99% of it adversely affects unintended targets including the public and environmental health [11]. In a study conducted in Northern Tanzania, it was reported that 50% of farmers apply up to 5 times or more recommended dosage of pesticides on crops and eventually 68% of them reported having fell sick after routine application of pesticides [12].…”
Section: Introductionmentioning
confidence: 99%